2013
DOI: 10.5005/jp-journals-10021-1161
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Anchorage using Mini-implants in the Maxillary Tuberosity Region

Abstract: Anchorage conservation has always been a challenge in orthodontics especially in cases requiring group movement of teeth. The drawbacks of conventional anchorage conservation methods like headgears and intermaxillary elastics have been overcome with the advent of skeletal anchorage. Mini-implants which have been proved successful in several intraoral locations for anchorage, can also be successfully placed in the maxillary tuberosity region. However, this site is not commonly used due to the fact that the dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…An implant success rate of 90% for group distal movement of teeth was suggested by Hyu-sang park et al, [6]. Reports from Sundaram Venkateswaran et al, [8,9], suggested high success rate of micro-implants and proper biomechanics for enmass retraction using skeletal anchorage in tuberosity and retromolar areas.…”
Section: Dentistry Section Abstractmentioning
confidence: 99%
“…An implant success rate of 90% for group distal movement of teeth was suggested by Hyu-sang park et al, [6]. Reports from Sundaram Venkateswaran et al, [8,9], suggested high success rate of micro-implants and proper biomechanics for enmass retraction using skeletal anchorage in tuberosity and retromolar areas.…”
Section: Dentistry Section Abstractmentioning
confidence: 99%